Training on Making and Testing the Efficacy of Hand Sanitizers from Lime and Sweet Orange Essential Oils for Pharmacy Students at Al-Muhtadin Vocational School Bekasi, West Java, Indonesia - Anindita, Reza; Putri, Intan Kurnia; Beandrade, Maya Uzia; Arianti, Anisa Rachmita; Futihat, Chilyati Eky (Jurnal Soeropati, 2025)
Community analysis shows that Al-Muhtadin Pharmacy Vocational School, Bekasi students are interested in making pharmaceutical products from natural ingredients. However, their desires are often hampered by the lack of knowledge regarding manufacturing pharmaceutical preparations from natural ingredients. Therefore, the solution is to hold training in hand sanitizers with natural ingredients from essential oils of lime and sweet orange peels. This Community Service activity (CSA) aims to provide training in making and testing hand sanitizers for Al-Muhtadin Pharmacy Vocational School students in Bekasi. The CSA participants numbered 62 students of Al-Muhtadin Pharmacy Vocational School, Bekasi. The activity methods include providing material on Clean and Healthy Living Behavior (CHLB) and making hand sanitizers, training in making and testing hand sanitizer products, and evaluation in the form of concept tests (pre-test and post-test) and skills tests. The paired t-test results showed that the calculated t-value was smaller than the t-table (-4.952 <-2.013), or there was a significant difference in the average value of knowledge about CHLB and making hand sanitizers between before and after being given the material. In contrast, the practical exam showed the average percentage value of participants' skills in making hand sanitizers of 90.57%, while the efficacy testing skills were 93.44%. Testing of the antibacterial efficacy of hand sanitizer products by respondents showed that they were able to inhibit and kill bacteria on the hands. This CSA concludes that all participants have learned the concept and skills regarding manufacturing and testing hand sanitizers from a combination of lime and sweet orange peel essential oils.